2020
DOI: 10.1080/02640414.2020.1803717
|View full text |Cite
|
Sign up to set email alerts
|

Continuous walking and time- and intensity-matched interval walking: Cardiometabolic demand and post-exercise enjoyment in insufficiently active, healthy adults

Abstract: We compared cardiometabolic demand and post-exercise enjoyment between continuous walking (CW) and time-and intensity-matched interval walking (IW) in insufficiently active adults. Sixteen individuals (13 females and three males, age 25.3 ± 11.1 years) completed one CW and one IW session lasting 30 min in a randomised counterbalanced design. For CW, participants walked at a mean intensity of 65-70% predicted maximum heart rate (HR max ) . For 36 IW, participants alternated between 3 min at 80% HR max and 2 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Morikawa et al [ 9 ] reported that fast walking training for 4 months increased the peak aerobic capacity and improved variables related to lifestyle diseases. However, the previous studies compared metabolic and cardiovascular adaptations between “fast interval walking” and “continuous walking” [ 10 , 11 ] and there has been no direct comparison between “fast walking” and “running”. During running, the energy expenditure (EE) increases linearly with running speed, while the EE during walking increased non-linearly, resulting in greater EE during walking compared with running above a certain speed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morikawa et al [ 9 ] reported that fast walking training for 4 months increased the peak aerobic capacity and improved variables related to lifestyle diseases. However, the previous studies compared metabolic and cardiovascular adaptations between “fast interval walking” and “continuous walking” [ 10 , 11 ] and there has been no direct comparison between “fast walking” and “running”. During running, the energy expenditure (EE) increases linearly with running speed, while the EE during walking increased non-linearly, resulting in greater EE during walking compared with running above a certain speed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One key approach to increase PA and health across the population is to promote walking for recreation and transport [17][18][19]. Walking is the most common type of leisure-time PA among adults, and is simple, costeffective, and with a strong potential to improve public health [20,21]. Walking speed (WS), measured as the time required to walk a given distance, is a common tool used to assess physical function [22].…”
Section: Introductionmentioning
confidence: 99%